Scott & Neil's Designing Web Interfaces Master Class - Neil, Theresa; Scott, Bill (O'Reilly Media, Incorporated, 2010)
Want to learn how to create great user experiences on today's Web? In this video master class, UI experts Bill Scott and Theresa Neil present design patterns for building web interfaces that provide rich interaction. Distilled from the authors' years of experience at Sabre, Yahoo!, and Netflix, these best practices are grouped into six key principles to help you take advantage of the web technologies available today. With an entire section devoted to each design principle, this class will help you: Make It Direct: Edit content in context with design patterns for In Page Editing, Drag and Drop, and Direct Selection Keep It Lightweight: Reduce the effort required to interact with a site by using In Context Tools to leave a "light footprint" Stay on the Page: Keep visitors on a page with overlays, inlays, dynamic content, and in-page flow patterns Provide an Invitation: Help visitors discover site features with invitations that cue them to the next level of interaction Use Transitions: Learn when, why, and how to use animations, cinematic effects, and other transitions React Immediately: Provide a rich experience by using lively responses such as Live Search, Live Suggest, Live Previews, and more